A Durable Fluorine‐Free MOF‐Based Self‐Cleaning Superhydrophobic Cotton Fabric for Oil‐Water Separation. Issue 13 (23rd March 2022) - Long, Zhiwen; Yuan, Luhan; Chen, Jianyu; Luo, Lei; Shi, Chu; Wu, Caiqin; Qiao, Hui; Wang, Keliang
Abstract: It is challenging to fabricate durable and fluorine‐free superhydrophobic surfaces through simple procedures. In this study, a novel fabrication method for constructing robust, wearable, and fluorine‐free superhydrophobic surfaces on cotton textiles has been achieved via in situ growth of zeolitic imidazolate framework‐8 (ZIF‐8) layers followed by polydimethylsiloxane (PDMS) modification. The roughness created by the sheet‐like structure is optimized by tuning the mole ratio between 2‐methylimidazole and zinc nitrate during the in situ growth, while polydopamine (PDA) is introduced to improve the durability and stability. The resultant PDA/ZIF‐8/PDMS@cotton fabric exhibits a maximum water contact angle of 156.4° and a low sliding hysteresis angle of 3.8°. The as‐prepared superhydrophobic fabric also presents excellent durability and stability, and outstanding resistance against continuous sunlight exposure and various chemical reagents. In addition, the superhydrophobic surface possesses excellent self‐cleaning and anti‐fouling performance, as well as high separation efficiency >97% and reusability when serving as a filter during the oil‐water separation. The proposed approach and prepared superhydrophobic fabric strongly demonstrate the potential applications in oil‐water separation with a prolonged life cycle. Abstract : A novel fabrication method for constructing robust, wearable and fluorine‐free superhydrophobic surfaces on cotton textiles is achieved via in situ growth of zeolitic imidazolate framework‐8 (ZIF‐8) layers followed by polydimethylsiloxane (PDMS) modification. The PDA/ZIF‐8/PDMS@cotton fabric possesses excellent superhydrophobic, self‐cleaning, and anti‐fouling performance, as well as high oil‐water separation efficiency >97% and reusability.